Digital Traceability in Halal Food Supply Chains A Bibliometric Analysis of IoT and Blockchain Applications - Kholid Albar; Dimas Wahyu Rozaki; Novie Andriani Zakariya (STEI Kanjeng Sepuh Gresik Jawa Timur, 2026)
The rapid growth of the global halal food industry has intensified the need for robust traceability systems to ensure product integrity, transparency, and compliance with religious standards. This study aims to analyze the development and structure of research on traceability technologies in halal food supply chains, with a focus on emerging digital solutions such as blockchain and the Internet of Things. A bibliometric approach was employed using Scopus-indexed publications from 2015 to 2025, combined with network visualization techniques to map research trends, key contributors, and thematic clusters. The results reveal a significant increase in research output over the past decade, with strong dominance from Southeast Asian countries, particularly Malaysia and Indonesia. Core research themes include traceability, halal certification, and supply chain management, with growing emphasis on digital technologies that enhance transparency and trust. Blockchain and Internet of Things technologies are identified as central enablers of real-time data integration and secure verification, although their adoption is constrained by cost, infrastructure, and regulatory fragmentation. The analysis also highlights the importance of certification bodies and governance frameworks in ensuring halal compliance and supporting system interoperability. Overall, the study demonstrates that halal traceability is evolving toward integrated, technology-driven systems, yet requires further development in terms of scalability and standardization. The findings provide valuable insights for researchers and policymakers, emphasizing the need for interdisciplinary approaches and regulatory harmonization to strengthen global halal supply chain systems.